Pengaruh Brand Image Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Iphone Dengan Gaya Hidup Sebagai Variabel Interverning - Fuji Lestari, Lutfiana (Philosophiamundi, 2023)
Along with the times in Indonesia, the growth of smartphone industry technology is currently experiencing a significant increase. Technology is growing rapidly with the many new things that accompany life today. The more advanced technology, the more positive impact on the development of various communication media. This study aims to determine and analyze the influence of brand image and product quality on purchasing decisions for iphone products with lifestyle as an intervening variable. In this study using quantitative data. The method used in collecting data is using a questionnaire that is measured by a Likert scale. The sampling technique in this study used a non-probability sampling technique with a total sample of 100 respondents. In processing this data using the SmartPLS program version 3.0. The results showed that brand image has a positive influence on purchasing decisions, product quality has a positive influence on purchasing decisions, brand image has an influence on lifestyle, product quality does not have a significant influence on lifestyle, lifestyle has a significant positive influence on purchasing decisions , lifestyle is used as an intervening variable between brand image and purchasing decisions there is full moderation, lifestyle is used as an intervening variable between product quality and purchasing decisions there is no significant effect and no moderation.